A risk governance approach to mitigating food system risks in a crisis: Insights from the COVID-19 pandemic in five low- and middle-income countries - Polman, D. F.; Selten, M. P. H.; Motovska, N.; Berkhout, Ezra D.; Bergevoet, R. H. M.; Candel, J. J. L. (Elsevier, 2023)
Research on food system responses to COVID-19 has remained largely disconnected from the broader risk governance scholarship. We connect both literatures by adopting a risk governance lens to study how governments have dealt with COVID-19 induced food system risks across different phases of the crisis. Studying responses in five low- and middle-income countries – Bangladesh, Ethiopia, Mexico, Nigeria and Vietnam – we find that food system risks and actors related to the food system were largely absent from initial risks assessment and policy responses, leading to growing food insecurity risks for vulnerable groups. Feedback and involvement from local governments and societal actors improved the capacities to assess and mitigate food system risks. We suggest developing future arrangements that involve actors with knowledge on food system risks to allow for more adequate responses.